Influence of the duration of aging the system Ti/Al2O3 in a hydrogen atmosphere on hydrogen sorption, and electrical conductivity of the film; Eastern-European Journal of Enterprise Technologies; Vol. 5, iss. 12 (95) - Sypchenko V. S. Vladimir Sergeevich; Kiseleva E. S. Evgeniya Sergeevna; Sigfusson T. I. Torsteinn Ingi; Lisichko E. V. Elena Vladimirovna; Semkina L. I. Lyudmila Iosifovna; Efremova N. A. Nataliya Aleksandrovna; Rudkovskaya V. F. Vera Fedorovna (2018, 2018)
Title screen